(6x-12)2=12

Simple and best practice solution for (6x-12)2=12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (6x-12)2=12 equation:


Simplifying
(6x + -12) * 2 = 12

Reorder the terms:
(-12 + 6x) * 2 = 12

Reorder the terms for easier multiplication:
2(-12 + 6x) = 12
(-12 * 2 + 6x * 2) = 12
(-24 + 12x) = 12

Solving
-24 + 12x = 12

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '24' to each side of the equation.
-24 + 24 + 12x = 12 + 24

Combine like terms: -24 + 24 = 0
0 + 12x = 12 + 24
12x = 12 + 24

Combine like terms: 12 + 24 = 36
12x = 36

Divide each side by '12'.
x = 3

Simplifying
x = 3

See similar equations:

| 0.3x-0.4(6-x)=0.9 | | -13s+3s=10 | | -3x*(5+-3)=51 | | -1.5x=-150 | | 15.2x=-2 | | -5(2x-4y)= | | 2w^2+3=-5w | | -2x-11=8x+9 | | N^2+4n=2 | | 50r^2+55r=-15 | | 4m-4m+2m+1=17 | | cos(2x)+3=-5cos(x) | | 12(4y-5)+51=48y-9 | | 50r+55r=-15 | | 12-24=-3x | | x^2-50x-1400=0 | | 6j-4j+j-3j+j=14 | | 25+(13+12)=x-25 | | 12-24=3x | | 9u-7u+-18=-16 | | 5(4x+6)=x+9 | | -6(2y+3)+6=-36 | | 5m^2=16-38m | | x+3=3-(-5+3) | | 7w-5w+w+2=20 | | 11d-9d-1=7 | | -.2x^2+10x+280=0 | | y=-0.91(12)+103.47 | | -(-5+3)+4x-2*2=50 | | 7x^2+21x=126 | | 8h+4h-7h-4h=18 | | 3x^2+40x-8=0 |

Equations solver categories